1996
DOI: 10.7863/jum.1996.15.10.707
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral portal venous blood flow alterations induced by hepatic masses: evaluation with color and pulsed Doppler sonography.

Abstract: We examined 29 patients with intra-and extrahepatic masses and 10 normal volunteers with duplex and color Doppler ultrasonography. Portal blood flow adjacent to the masses was categorized as anterograde, retrograde, or nondetectable and was correlated with lesion size, character, and location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, arterioportal shunting is now recognized to occur in benign lesions as well ( Fig 10) (18). Moreover, hepatofugal flow can occur in juxtalesional portal veins in the absence of intralesional shunting if the lesion compresses and obstructs regional hepatic venous outflow, thus leading to shunting of regional hepatic artery inflow into a regional portal vein, which is transformed into an outflow tract for the shunted blood (19,20). Similarly, it has been shown that regional portal veins are transformed into draining veins for hepatic artery inflow during occlusion of regional hepatic venous drainage (21).…”
Section: Differential Diagnosis Arterioportal Fistulamentioning
confidence: 99%
See 1 more Smart Citation
“…However, arterioportal shunting is now recognized to occur in benign lesions as well ( Fig 10) (18). Moreover, hepatofugal flow can occur in juxtalesional portal veins in the absence of intralesional shunting if the lesion compresses and obstructs regional hepatic venous outflow, thus leading to shunting of regional hepatic artery inflow into a regional portal vein, which is transformed into an outflow tract for the shunted blood (19,20). Similarly, it has been shown that regional portal veins are transformed into draining veins for hepatic artery inflow during occlusion of regional hepatic venous drainage (21).…”
Section: Differential Diagnosis Arterioportal Fistulamentioning
confidence: 99%
“…Another rare exception is hepatofugal flow caused by a congenital portosystemic collateral vessel (39). Hepatofugal flow in one or more solely intrahepatic portal veins can occur in patients with a focal arterioportal shunt and is therefore not specific for portal hypertension (19).…”
Section: Diagnosis Of Portal Hypertensionmentioning
confidence: 99%
“…A hypovascular area peripheral (distal) to the abscess could also be observed, probably caused by perifocal edema or defective venous perfusion [11]. Color Doppler sonography may detect reversal flow in portal veins adjacent to liver abscesses [12], and these hemodynamic changes may also be detected on contrast-specific sonography.…”
mentioning
confidence: 98%
“…We theorize the peripheral and subcapsular tumor characteristic in the patients in our series may have contributed to the spontaneous regression. The more peripheral location could predispose the tumor to ischemia given the more tenuous blood supply, particularly in cirrhotic livers and subcapsular masses [12] . Furthermore, the subcapsular location and potentially local disruption of the capsule may predispose a lesion for immunologic presentation.…”
Section: Discussionmentioning
confidence: 99%